Rs1840680 single nucleotide polymorphism in Pentraxin 3: a potential protective biomarker of severe community-acquired pneumonia. Issue 4 (April 2021) - Zeng, Qiaojun; Tang, Tiantian; Huang, Biru; Bu, Shiyi; Xiao, Yingqi; Dai, Yumeng; Wei, Zixin; Huang, Linjie; Jiang, Shanping
Objective: Single nucleotide polymorphisms (SNPs) of pentraxin 3 ( PTX3 ) are associated with various outcomes of lung infections. This study aimed to analyze the relationship between PTX3 polymorphisms and the severity of community-acquired pneumonia (CAP). Methods: This is a retrospective case-control study comprising 43 patients with severe CAP (SCAP) and 97 patients with non-severe CAP. Three SNPs in the PTX3 gene (rs2305619, rs3816527, and rs1840680) from peripheral blood samples were genotyped by real-time polymerase chain reaction. The association between each SNP and the CAP severity was analyzed by logistic regression analysis. Results: We found that the rs1840680 polymorphism was significantly associated with CAP clinical severity. However, no such association was observed for the genotypes and allele frequencies of rs2305619 or rs3816527. The PTX3 rs1840680 AG genotype was an independent factor for a lower risk of SCAP after multivariate logistic regression analysis. Male sex and coronary heart disease were associated with an increased risk of SCAP. Conclusions: The PTX3 rs1840680 AG genotype was found to be associated with a lower risk of SCAP, and may serve as a potential protective biomarker to help clinical judgment and management.